Genetic analysis of yield and resistance to anthraconse in chilli(Capsicum annuum L) - Ajith P M (Department of Plant Breeding and Genetics, College of Agriculture, 2004)
Chilli (Capsicum annuum L) is an important spice cum vegetable crop, grown on a commercial scale in India. It is an important constituent of many foods since it adds flavour, colour, vitamin C and pungency. Productivity of the crop remains low mostly due to destructive diseases. One of the most dreaded diseases affecting chilli is anthracnose, which is also called dieback and fruit rot. The best way to tackle this disease is to grow resistant varieties. Hence it is essential to identify the sources of anthracnose resistance and study the inheritance of resistance to develop high yielding anthracnose resistant varieties of chilli. Therefore, an investigation was undertaken to reveal the genetic variability and to identify the resistant genotypes in a collection of germplasm, to estimate the combining ability and heterosis by line x tester analysis and to assess the inheritance pattern of anthracnose resistance and yield using generation mean analysis in order to formulate an appropriate breeding programme for improving the economic characters. Chilli germplasm consisting of 76 genotypes was evaluated simultaneously for anthracnose resistance and yield traits as two parallel field experiments in RBD with two replications during rabi 2002. Screening of germplasm for anthracnose resistance was carried out by recording per cent disease incidence and disease intensity at 30 DAT, 45 DAT and 60 DAT (Days After Transplanting). Majority of the genotypes showed disease incidence in the range of 20 to 30 per cent at 30 DAT, 45 DAT and 60 DAT. Three genotypes showed less than 10 per cent disease incidence at all the three stages. With regard to disease intensity, number of susceptible genotypes increased gradually from 30 DAT to 60 DAT with three genotypes remaining moderately resistant at all the three stages. Evaluation for yield traits revealed significant variations among the genotypes for 14 traits viz., days to first flowering, number of branches, number of fruits per plant, average green fruit weight, fruit weight per plant (yield), fruit length, fruit girth, number of seeds per fruit, hundred seed weight, plant height, duration of the crop, harvest index, capsaicin content and oleoresin content. The maximum values of both phenotypic and genotypic coefficients of variation were noticed for fruit weight per plant. All the traits possessed high heritability especially fruit weight per plant, fruit length, number of seeds per fruit, capsaicin content and hundred seed weight. Maximum genetic advance (% of mean) was observed for fruit weight per plant followed by number of fruits per plant, number of seeds per fruit and average green fruit weight. Correlation analysis indicated that most of the character combinations had higher genotypic correlation coefficients than phenotypic correlations. Fruit yield displayed positive genotypic association with number of branches per plant, number of fruits per plant, average green fruit weight, fruit length, fruit girth, hundred seed weight, duration of the crop, harvest index, capsaicin content, percent disease incidence and disease intensity and negative correlation with days to first flowering. Among the eight component traits, which had high association with fruit yield, the maximum positive direct effect was exerted by disease intensity followed by harvest index and number of fruits per plant. The highest negative direct effect was exerted by per cent disease incidence. Selection indices were computed utilizing fruit yield and its 13 component characters. Based on the selection indices, five high yielding anthracnose susceptible types viz., Jwalamukhi (L1), Jwalasakhi (L2), Muvattupuzha Local-1 (L3), Samkranthi Local-1 (L4) and Vaikom Local-2 (L5) were used as lines and three anthracnose resistant types viz. Pant C-1 (T1), Kidangoor Local-1 (T2) and Ujwala (T3) were used as testers for the line x tester analysis. From line x tester analysis high values of gca effects were noticed for fruit yield, number of seeds per fruit and number of fruits per plant. High values of sca effects were recorded for yield, number of seeds per fruit and per cent disease incidence. L1 was the most superior line which excelled with respect to mean performance and general combining ability for days to first flowering, number of fruits per plant, average green fruit weight, fruit yield, fruit girth, hundred seed weight, harvest index, per cent disease incidence and disease intensity. Among the testers, T2 was the best with respect to mean performance for fruit yield, average green fruit weight, fruit length, hundred seed weight, number of branches, plant height and harvest index. T3 showed the best general combining ability for yield and yield related attributes, per cent disease incidence and disease intensity. Among the fifteen hybrids evaluated with respect to per se performance, standard heterosis and sca effects, L1T3 (Jwalamukhi x Ujwala) and L2T3 (Jwalasakhi x Ujwala) were superior with regard to days to first flowering, average green fruit weight, fruit weight per plant, fruit length, fruit girth, plant height and anthracnose resistance. T3 a good general combiner for almost all the traits was a common parent in the two outstanding crosses. The two superior crosses viz. L1T3 (Jwalamukhi x Ujwala) and L2T3 (Jwalasakhi x Ujwala) were utilized for generation mean analysis in order to detect the gene action with regard to the various traits. Presence of epistasis was tested and subsequently interaction effects viz. additive x additive, additive x dominance and dominance x dominance effects were computed.